REITERATION USED ON DESCRIPTIVE TEXT OF THE TENTH GRADERS OF SMA N 1 MAGELANG IN THE SCHOOL YEAR OF 2018/2019 - Yoshinta Adinda Bayu (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Based on Curriculum 2013, the tenth grade students of senior high school should learn how to write a descriptive text. In composing a descriptive text, they also need to consider the use of reiteration in order to easily write a text by varying the word choice, therefore the researcher focuses on reiteration used in students descriptive text. There are two objectives of the research. The first objective is to describe the types of reiteration. The second objective is to explain the most dominant type of reiteration in descriptive texts written by tenth graders. This research uses descriptive qualitative approach. The subject of the research is descriptive texts written by X IPA 5 Class of SMA N 1 Magelang in the school year 2018/2019. The data is analyzed by using Tanskanen’s Theory (2006). The steps of data analyzing are 1) identifying reiterated items from students’ descriptive texts, 2) analyzing the categories of reiteration, 3) classifying the types of reiteration and summing up the total of reiteration, 4) calculating the percentage of reiteration, and 5) concluding the results. The result of this research shows 311 reiterated items occured in 15 descriptive texts that have been analyzed. It presents all of reiteration types exist in the students’ descriptive text. Simple repetition becomes the most dominant type of reiteration that occurs 88 times spread to all of descriptive texts. The considerable factor is because simple repetition is the most straightforward reiteration type.